Reconstructing Corporate Environmental Criminal Liability in Indonesia: Harmonizing Substantive Environmental Law and the 2025 Criminal Procedure Code - Muammar Alay Idrus (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2026)
This study examines the effectiveness of corporate punishment in environmental crime cases in Indonesia amid implementation deficits and procedural fragmentation by analyzing the harmonization between substantive environmental criminal law and corporate criminal procedure. It assesses the application of corporate criminal liability under Law Number 32 of 2009, evaluates sentencing practices, and formulates an integrated model of corporate environmental punishment following the 2025 Criminal Procedure Code. Using normative legal research with a statutory approach and supported by a systematic literature review, the study finds that although corporations are formally recognized as subjects of environmental criminal law, judicial practice is dominated by monetary fines, while additional sanctions and environmental restoration measures are rarely imposed. This indicates an implementation deficit rather than normative inconsistency, weakening deterrence and allowing sanctions to be treated as a business cost. The study argues that Chapter XVIII of the 2025 Criminal Procedure Code provides a clearer procedural framework for prosecution, sentencing, and environmental restoration, enabling structural–procedural harmonization. It proposes an integrated model aligning substantive norms with procedural enforcement and concludes that the core issue lies in procedural fragmentation and weak implementation.